Functional analysis of the short splicing variant encoded by CHI3L1/YKL-40 in glioblastoma - Shi, Mengqi; Ge, Qianyun; Wang, Xinrong; Diao, Wenbin; Yang, Ben; Sun, Sipeng; Wang, Guohui; Liu, Tian; Chan, Andrew Man-Lok; Gao, Zhiqin; Wang, Yi; Wang, Yubing (Frontiers in Oncology, 2022)
The glycoprotein YKL-40 has been well studied as a serum biomarker of prognosis and disease status in glioblastoma. YKL-40 is chitinase-like protein with defected chitinase activity, plays important roles in promoting cell proliferation, migration, and metastasis in GBM. The short variant (SV) of YKL-40, generated by an alternative splicing event that spliced out the exon 8, was reported in the early developing human musculoskeletal system, while its role in GBM was still unknown. Our results showed that individual glioblastoma cell lines displayed increased expression of the short variant of YKL-40 after low serum treatment. In addition, unlike the full-length (FL) version, which was localized to all cell compartments, the short isoform could not be secreted and was only localized to the cytoplasm. Functionally, FL YKL-40 promoted cell proliferation and migration, whereas SV YKL-40 suppressed them. Transcriptome analysis revealed that these opposing roles of the two isoforms may modulate via differently regulating several oncogenic related pathways, including P53, G2M checkpoint and MYC related signaling. This study may provide new ideas for development of anti-YKL-40 targeted therapy in GBM treatment.